Assessing adverse childhood experiences, social, emotional, and behavioral symptoms, and subjective health complaints among Hungarian adolescents - Beáta Kovács-Tóth; Barnabás Oláh; Gábor Papp; Ildikó Kuritárné Szabó (BMC, 2021)
Abstract Background Adverse Childhood Experiences (ACEs) can have lifelong adverse impacts; they can play a role in the development of subsequent emotional, cognitive, and social impairments leading to somatic and mental difficulties, as well as health damaging behaviours. Unfortunately, there are currently no research data available in Hungary regarding the frequency of ACEs among adolescents. Aims A cross sectional questionnaire survey was conducted in a community sample of Hungarian adolescents to assess the frequency of ACEs and analyse their association with current social, emotional, and behavioural symptoms (SEB), and subjective health complaints (SHC). Methods Demographic data, ACEs, SEB and SHC status of 516 adolescents aged 12 to 17 were collected. ACEs were assessed using the ACE Score Calculator; for SEB the Strengths and Difficulties Questionnaire, and for SHC some specific items from the Health Behaviour of School Children questionnaire were employed. To analyse the relationship of ACEs to SEB and SHC logistic regression was performed. Results Our results showed that the frequency of ACEs, SEB and SHC is high among adolescents. One-fourth of the students reported ≥ 2 categories of childhood exposures, and 7.4% reported having experienced ≥ 4 types of ACEs. The most prevalent forms of child maltreatment were emotional neglect (15.5%) and emotional abuse (14.5%). The most frequent dysfunctional household condition was parental divorce or separation (23.8%), followed by household substance abuse (8.9%) and household mental illness (8.1%). Almost one-fifth of students (17.5%) reported SEB symptoms (peer relationship problems in 21.7%, emotional symptoms in 14.6%, conduct problems in 18.3%, hyperactivity in 15%). The prevalence of SHC was also high: more than half of the students experienced at least one subjective health complaint multiple times a week. Significant associations were found between ACEs and the SEB/SHC reported by students. Conclusions Adverse childhood experiences, social, emotional, and behavioural symptoms, and SHC are common among Hungarian adolescents. The cumulation of ACEs is associated with a higher number of SEB and SHC symptoms. Therefore, prevention programmes, early recognition, risk reduction, and therapy are needed.